Implementation of the Simple Additive Weighting Method in Determining Recipients of Subsidized Food Materials for Poor Families - Kusmanto, Kusmanto; Budi, Eko Setia; Samsir, Samsir; Hariska, Elvia; Ginting, Guidio Leonarde (Forum Kerjasama Pendidikan Tinggi, 2021)
In accordance with the rules that have been set from the Village Office so that the community gets subsidized food, it must comply with the specified criteria. The Village Office will determine who is selected to receive subsidized food and distribute it to poor families. As a tool that can be used to determine someone who is eligible to receive subsidized food, a decision support system is needed. In the decision support system there are several methods, one of which can be used is the SAW (Simple Additive Weighting) method. In this research